THE EFFECT OF PRODUCT QUALITY ON REPURCHASE INTENTION MEDIATED BY CUSTOMER SATISFACTION (A Study on Toyota Car Consumers) - Pande Erlangga Raewangsa; I Wayan Santika (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The rapid development of the automotive industry in Indonesia compels companies to continuously innovate in order to face increasingly intense competition. Toyota, as one of the market leaders, faces the challenge of declining sales despite having a large customer base. This phenomenon raises the question of whether product quality directly drives repurchase intention, or whether other factors mediate the relationship. This study aims to examine the effect of product quality on repurchase intention with customer satisfaction as a mediating variable among Toyota consumers in Denpasar. A quantitative approach with a causal design was employed. Data were collected through questionnaires distributed to existing Toyota customers at PT Astra International Auto2000 Sanur, with a sample size ranging from 55 to 110 respondents, determined through purposive sampling. The variables used included product quality (X), customer satisfaction (M), and repurchase intention (Y), each measured with specific indicators based on established theories and previous studies. Analysis was conducted to determine both the direct and indirect relationships among variables. The findings reveal that product quality does not have a significant effect on repurchase intention. However, product quality has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction exerts a positive and significant influence on repurchase intention and significantly mediates the relationship between product quality and repurchase intention. These results emphasize that consumer loyalty is not solely determined by product quality but also by the level of satisfaction experienced after product usage. Therefore, enhancing customer satisfaction becomes a key strategy for Toyota in maintaining consumer loyalty and competitiveness in the Indonesian automotive market.